2017
DOI: 10.5222/buchd.2017.203
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of ultrasonography guided transversus abdominis plane block and wound infiltration for pediatric inguinal hernia repair: Randomised clinical study

Abstract: ÖZAmaç: Transversus abdominis plan (TAP) blokun postoperatif analjezik etkinliği abdominal cerrahi geçirecek olan hastalarda tartışmalıdır. Bu çalışmanın amacı, inguinal herni tamiri yapı-lan pediyatrik hastalarda ultrasound eşliğinde yapılan TAP blok ile yara yeri infiltrasyonunun analjezik etkinliğini karşılaştırmaktır. Yöntem: Etik onam alındıktan sonra 3-8 yaş arası, tek taraflı inguinal herni onarımı yapılacak olan 60 hasta randomize olarak TAP blok (Grup TAP, n=30) veya yara yeri infiltrasyonu (Grup infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[29] A meta-analysis showed that selected pre-emptive analgesia such as epidural analgesia, local wound infiltration, and systemic NSAID administration generally had a beneficial effect from traditional analgesic regimens. [30] In a recent pediatric inguinal hernia repair study, Ahıskalıoğlu et al [31] showed an average of 5.9±3.0 for pain scores in the PWI group up to the first 24 h postoperatively. In a recent study comparing wound infiltration and TAP block, the authors reported the mean pain scores in the PWI group mean mCHEOPS score=7.0, the time of the first analgesic requirement 4.7±1.6 h, and total acetaminophen consumption as 53.0±6.4 mg/ kg.…”
Section: Discussionmentioning
confidence: 98%
“…[29] A meta-analysis showed that selected pre-emptive analgesia such as epidural analgesia, local wound infiltration, and systemic NSAID administration generally had a beneficial effect from traditional analgesic regimens. [30] In a recent pediatric inguinal hernia repair study, Ahıskalıoğlu et al [31] showed an average of 5.9±3.0 for pain scores in the PWI group up to the first 24 h postoperatively. In a recent study comparing wound infiltration and TAP block, the authors reported the mean pain scores in the PWI group mean mCHEOPS score=7.0, the time of the first analgesic requirement 4.7±1.6 h, and total acetaminophen consumption as 53.0±6.4 mg/ kg.…”
Section: Discussionmentioning
confidence: 98%
“…By affecting the ventral ramus of the thoracolumbar nerve, the skin, muscle and parietal peritoneum of the anterior abdominal wall are blocked. Thus, effective analgesia is provided, especially for lower abdominal, gynaecological and urological procedures (9). Caudal epidural block is made by applying local anaesthetic agent to the sacral canal passing the sacrococcygeal ligament, and is an often preferred regional anaesthesia method in pediatric lower extremity, pelvic and below the umbilicus surgical procedures (10).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients can be mobilized, and some suitable patients can be even discharged on the same day of surgery thanks to the implementation of appropriate surgery and analgesia (2) . However, inadequate postoperative analgesia may cause irritability in children due to pain and dissatisfaction in parents and may lead to chronic pain in the later stages of the children's life (3) .…”
Section: Introductionmentioning
confidence: 99%